Being a Parent Together: Parental Role Salience Promotes an Interdependent Self-Construal - Li, Yuanyuan Jamie; Gong, Han (Frontiers in Psychology, 2018)
Although how people construe themselves is often deemed as a chronic and stable individual difference, self-construal has been shown to be exert consequential influences on thinking and doing. Yet, relatively little is known about the factors that could potentially shape the extent to which individuals form an independent-self or an interdependent-self. In the current work, we try to explore whether and how the salience of parental roles would affect self-construal. Given that an interdependent self-construal helps individuals maintain connectedness and harmony with others in a group, which is adaptive for being a parent, we propose that parental roles tend to increase the perceived connection with the others, thus leading to an interdependent self-construal. Findings from three studies consistently show that the salience parental role promotes an interdependent self-construal. Moreover, we observe that parents’ role salience only prompts an interdependent self-construal in relation to other people without increasing the connection with one’s future self. Theoretical and practical implications of our findings are discussed.